Local Wisdom-based Thematic Teaching Materials - Dewi, Nina Ardianti; Ramadan, Zaka Hadikusuma (Universitas Pendidikan Ganesha, 2021)
The lack of innovative teaching materials in the learning process causes students to have difficulty learning independently. In addition, the teaching materials provided by the teacher are general and have not been integrated with local wisdom. This causes students to have difficulty understanding the material that has an impact on learning outcomes. The purpose of this research is to create thematic teaching materials based on Riau's local wisdom. The type of research conducted is R&D with the ADDIE model. However, only three stages (analyze, Design, and Development) were carried out. The subjects of this study were 6 experts, consisting of 2 material experts, 2 linguists, 2 design experts, and fourth-grade elementary school students. Data collection methods used are interviews and validation sheets. The analysis carried out is a qualitative and quantitative analysis of interview data and validation sheets. The study results stated that thematic teaching materials based on Riau's local wisdom were feasible from the aspect of material, language, and design with an average score of 89.33% with very valid categories. So, thematic teaching materials based on Riau local wisdom are feasible to use. The research implication is that teachers in learning can use the developed teaching materials.